ANALISIS PERBANDINGAN USER EXPERIENCE APLIKASI PEMESANAN KOPI TOMORO COFFEE DAN KOPI KENANGAN MENGGUNAKAN METODE USER EXPERIENCE QUESTIONNAIRE (UEQ) (Kohesi: Jurnal Sains dan Teknologi, 2025)
The growth of coffee ordering applications in Indonesia demands an improvement in user experience (UX) quality to remain competitive in the digital space. Tomoro Coffee and Kopi Kenangan are two popular brands, yet there have not been many studies comprehensively comparing the user experience of both. This research aims to analyze and compare the UX of the two applications using the User Experience Questionnaire (UEQ) method, which covers six main dimensions: attractiveness, clarity, efficiency, accuracy, stimulation, and novelty. A total of 162 valid respondents participated in the online survey, and the data were analyzed using the official UEQ analysis tool and a t-test. The results show that Tomoro Coffee excels in efficiency, while Kopi Kenangan performs better in clarity and accuracy. Both applications received positive scores across all dimensions, classified as "Good" to "Excellent." These findings provide practical insights for app developers to enhance UX based on empirical evidence and contribute to academic literature on local mobile app UX in Indonesia.